2012
DOI: 10.1590/s1020-49892012000700013
|View full text |Cite
|
Sign up to set email alerts
|

Perfil epidemiológico dos casos de gripe A na região sul de Santa Catarina, Brasil, na epidemia de 2009

Abstract: The studied sample differed from the national profile of influenza A cases in Brazil by the absence of associated comorbidities. However, it was similar to the national profile in terms of the young age of cases and the significant association with fever, cough, and dyspnea. An extension of the annual immunization campaign (currently focused on risk groups) to the overall population should be considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
13

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 8 publications
1
3
0
13
Order By: Relevance
“…As a result of our study, among the total of reported cases, the highest frequency occurred in females, children and young adults who are white, with an educational level of completed high school and residents in urban areas were the most frequently notified, as well as confirmed cases of influenza A(H1N1)pdm09 were found. Such findings are supported by results of other authors 20,21,[23][24][25][26][27][28] .…”
Section: Description By Time Place and Individualsupporting
confidence: 91%
“…As a result of our study, among the total of reported cases, the highest frequency occurred in females, children and young adults who are white, with an educational level of completed high school and residents in urban areas were the most frequently notified, as well as confirmed cases of influenza A(H1N1)pdm09 were found. Such findings are supported by results of other authors 20,21,[23][24][25][26][27][28] .…”
Section: Description By Time Place and Individualsupporting
confidence: 91%
“…A taxa de letalidade encontrada em nosso estudo é se-melhante àquela observada em outros estudos publicados 19,26,28,50,51,52,53,54,55,56,57,58,59,60,61,62,63,64,65,66 .…”
Section: Discussionunclassified
“…Diversos autores citam que, entre as limitações dos estudos com dados secundários, está a qualidade dos dados: dificuldade e heterogeneidade no preenchimento do instrumento, subnotificação e inexatidão dos dados coletados, prioridade de registro dos casos graves ou dos que pertencem aos grupos de risco 19,25,30,45,54,60,66 .…”
Section: Limitaçõesunclassified
“…É preciso destacar também que o registro de óbito por pneumonia pode ser influenciado por outras infecções de vias aéreas não prevenidas pela vacina PCV10 35 , tais como a influenza A (H1N1) que pode originar um quadro de pneumonia 36,37 . Porém, esse cenário não foi observado, pois apenas no Planalto Norte ocorreu uma pequena elevação na taxa de mortalidade por pneumonia no período da epidemia da influenza A (H1N1), e em todo o estado, apenas um óbito em criança menor de um ano de idade foi atribuído à influenza, no ano de 2009.…”
Section: Tabelaunclassified